Gnosis und Judentum : Alttestamentliche und jüdische Motive in der gnostischen Literatur und das Ursprungsproblem der Gnosis. - Lahe, Jaan (BRILL, 2011)
The book analyses different theories concerning the origin of Gnosticism and the use of lore from the Old Testament and Judaism in Gnostic literature and searches for an answer to the following question - could the use of lore from the Old Testament and Judaism in Gnostic literature validate the theory that Gnosticism is of Jewish origin?
Keywords: Gnosticism -- Relations -- Judaism.; Judaism -- Relations -- Gnosticism.; Gnostic literature -- Relation to the Old Testament.; Littérature gnostique -- Relation avec l'Ancien Testament.; Gnosticisme -- Relations -- Judaïsme.; Judaïsme -- Relations -- Gnosticisme.; RELIGION -- History.; Gnostic literature -- Relation to the Old Testament; Gnosticism; Interfaith relations; Judaism